Hubungan sistem amaran awal banjir dengan tahap kesediaan masyarakat menghadapi bencana banjir di Pantai Timur Semenanjung Malaysia - Nurul Aini, Mehat (2019)
The problem of community readiness in facing flood disaster in the East Coast of Peninsular Malaysia still exists even though flood’s early warning system has long been operating. The objectives of the study are first, to determine the level of readiness of the community members about the flood’s early warning system. Second, to evaluate the relationship between the flood’s early warning system with the Kelantan and Terengganu community’s readiness and third, to analyze the difference in the community’s readiness in facing flood disaster. The sample of the study involves 1,536 people from four districts namely Kota Bharu, Kuala Krai, Kuala Terengganu and Kemaman. The data were analyzed using the descriptive techniques, Pearson correlation and ANOVA one way based on the research objectives. With regard to research objective one, the finding shows that Terengganu community has a higher readiness level of 91.51 percent compared to Kelantan community, which is 88.01 percent. With regard to research objective two, the results show that all relationships between the two states received H1 and Kelantan has higher significant relationship, i.e., r =.661 compared to Terengganu, i.e., r =.566. Finally, with regard to research objective three, the results show that the difference in the community’s readiness to face the flood disaster for cognitive readiness significantly exists at 10 percent; affective difference significantly exists at seven percent; and the psychomotor difference significantly exists at 11 percent. Hence, the findings show that early warning system affects the community’s readiness in facing flood disaster but the destruction of property and the loss of life is still on the rise. Thus the study opines that there are other factors that may cause death and property destruction. The study, therefore, suggests that there is a need to improve awareness programs and early education on flood disaster in order to change the community’s readiness which is now at a low level to become more positive in facing any possible flood disaster in the future.